Nav channels in cancers: Non-classical roles - Hengrui Liu (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Voltage-gated sodium channels (Nav channels) are transmembrane proteins that allow the permeability of sodium ions across membranes. They are critical for the initiation of the action potential. Research has revealed that Nav channel α and β subunits expressed abnormally and play non-classical roles in some cancer types. However, the understanding of Nav channel proteins in cancers remains insufficient and the lack of specific Nav channel drugs impedes the study in this field. The purpose of this mini-review is to summarize and comment on the present understanding of the roles of Nav channels in cancers. The membrane potential in non-excitable cells is critical for cell activities. Cancer cells usually have a higher resting membrane potentials than non-cancer cells. Nav1.5 and Nav1.7 are the two most expressed Nav channels in human cancers, while Nav1.2 and Nav1.6 are also expressed in some cancer types. There are several mechanistic speculations for the role of Nav channels in cancer, which include sodium-other ions homeostasis, the β subunits, and humoral regulation. To be mentioned, the review includes some personal perspectives that are required for further validation. This review will be conducive to the field of Nav channels in cancers.